Titration of inspired oxygen in preterm infants with hypoxemic respiratory failure using near‐infrared spectroscopy and pulse oximetry: A new approach. Issue 12 (21st September 2021) - Elsayed, Yasser N.; Dakshinamurti, Shyamala
Abstract: Background: Titration of inspired oxygen is a challenge in preterm infants with hypoxemic respiratory failure (HRF). Monitoring of brain oxygen by near‐infrared spectroscopy (NIRS) has been proven to minimize the burden of hyperoxia and hypoxemia; with a better understanding of cerebral autoregulation, integrating NIRS and pulse oximetry for titrating inspired oxygen in preterm infants is a novel approach. Methods: We studied the impact of integrated monitoring of oxygen saturation by pulse oximetry (SpO2 ) and cerebral regional tissue oxygen (crRTO) by NIRS during a stepwise oxygen reduction test (ORT) on reducing oxygen requirement in preterm infants with HRF. The correlation between SpO2 with crRTO, and fractional oxygen extraction (FOE) was assessed, concordance levels ( r  > 0.5) were determined during the assessment period and were considered as a sign of impaired autoregulation. The primary outcome was the achievement of significantly lower FiO2 at 72 h after the start of the integrated monitoring. Results: A total of 38 preterm infants were included, 27 had normal cerebral autoregulation (CAR) (Group 1) in whom SpO2 was poorly correlating with crRTO with ( r  < 0.5) and had a significantly greater percentage of reduction below baseline in FiO2 (mean: 34%). Eleven infants had impaired CAR (Group 2) with SpO2 significantly correlating with crRTO ( r  > 0.5) and had a linear trend of FOE inverse to SpO2 and crRTO; this was considered as an arterial saturation dependent oxygen delivery (SadDO2 ). Conclusion: Integrated monitoring of preterm infants by SpO2 and crRTO was associated with easier weaning of oxygen with less burden of both hyperoxia and hypoxemia.